Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0002-9440(10)64954-1
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Association between the Human Heat Shock Transcription Factor 1 (HSF1) and Prostate Adenocarcinoma

Abstract: A search for differentially expressed genes in a pair of nonmetastatic (PC-3) versus metastatic variant (PC-3M) human prostate carcinoma cell lines led to identification of the human heat shock factor (HSF1) as an overexpressed gene product in PC-3M cells. Analysis of primary prostate cancer specimens indicated that HSF1 is generally up-regulated in most of the malignant prostate epithelial cells relative to the normal prostate cells. Among the known effectors of HSF1 action, constitutive levels of HSP70 and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 34 publications
(35 reference statements)
6
104
0
3
Order By: Relevance
“…The heat shock element was present in the promoter region of many genes such as HSP90, HSP27, HSP70 and drug resistant gene MDR1 [21] . Hoang [22] recently reported HSF1 expression was increased in a prostate cancer cell line. Our study not only provided the first evidence to demonstrate the association of HSF1 gene expression and CRC, but also suggested that the induction of HSF1 gene expression might be associated with a broad range of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The heat shock element was present in the promoter region of many genes such as HSP90, HSP27, HSP70 and drug resistant gene MDR1 [21] . Hoang [22] recently reported HSF1 expression was increased in a prostate cancer cell line. Our study not only provided the first evidence to demonstrate the association of HSF1 gene expression and CRC, but also suggested that the induction of HSF1 gene expression might be associated with a broad range of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock factor 1 is overexpressed in human prostate cancer cells. 61 Although there is no previous information on the expression of HSF-2 in the bladder, a recent report indicates that urothelial cells can respond to urine of IC patients with a modest alteration in a 72-kd stress protein. 36 It has been shown that heat shock proteins and stress can reduce the inflammatory response.…”
Section: Heat Shock Transcription Factormentioning
confidence: 99%
“…Homology between the amino-acid sequences of human HSFs is only 30-40%, and evidence for specific functions of HSFs beyond heat-shock response is speculative. Many types of tumors contain high concentrations of HSPs of the HSP27, HSP70 and HSP90 families (Hoang et al, 2000;Cen et al, 2004). The roles of HSPs in tumor development may also be related to their functions in the development of tolerance to applied stress (Li and Werb, 1982).…”
Section: Introductionmentioning
confidence: 99%